The Practice of Lending Names (Nominees) in the Perspective of Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes - Sellyne Anggraeni; Winarsih (Law Research Review Quarterly, 2026)
The practice of lending names (nominees) is often found in corporate ownership structures and financial transactions in Indonesia. Although it is not specifically regulated as a separate offense under Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes (TPPU Law), this practice is frequently used to conceal the origin of assets and obscure the identity of the beneficial owner. This research aims to analyze the legal position of nominee practices within the framework of the TPPU Law and to determine the criteria under which a nominee may be held criminally liable. Using normative legal research with statutory and conceptual approaches, this study examines the TPPU Law, the National Criminal Code (Law No. 1 of 2023), criminal law doctrines, FATF Guidelines 2023, and relevant court decisions. The findings show that the TPPU Law does not criminalize nominee status alone, but rather emphasizes the perpetrator’s conduct and mental element. Referring to Articles 3, 4, and 5 of the TPPU Law, now reflected in Article 607 paragraph (1) of the National Criminal Code, a nominee may be prosecuted if two main criteria are fulfilled: first, committing a concrete act included in the offense formulation (actus reus); second, knowing or reasonably suspecting that the managed assets originate from criminal activity (mens rea). Economic benefits received by the nominee can also strengthen indications of intent or negligence. Therefore, law enforcement must clearly distinguish between low-risk nominees who act without knowledge and high-risk nominees who knowingly participate in money laundering schemes.